Exogenous kisspeptin enhances seasonal reproductive function in male Siberian hamsters. (30th March 2017) - Bailey, Allison M.; Legan, Sandra J.; Demas, Gregory E.
Summary: Animals living in temperate climates are faced with the challenge of reproducing only when environmental conditions are suitable for offspring survival. Environmental cues signalling current and future energy availability (e.g., food availability and photoperiod respectively) are used to appropriately time reproduction. The precise neuroendocrine mechanisms regulating reproduction in response to these cues are unknown. The goal of the present study was to investigate a functional role for kisspeptin, a neuropeptide that shows promise as a key regulator of seasonal reproduction, in integrating multiple environmental cues to regulate reproduction in the Siberian hamster ( Phodopus sungorus ). Siberian hamsters undergo robust gonadal regression and terminate reproduction in unsuitable environments [short winter‐like day lengths (photoperiods), low food availability]. Adult male hamsters were housed in short‐day or intermediate photoperiods, received either ad‐libitum access to food or mild food restriction, and were treated with either kisspeptin or a vehicle for 6 weeks to determine the ability of kisspeptin to attenuate gonadal regression. Hamsters exhibited varying degrees of gonadal regression in response to inhibitory environments (short‐day photoperiod, food restriction). Kisspeptin treatment successfully enhanced testis mass under these inhibitory conditions, but did not affect normal seasonal changes in body mass and food intake. Thus, kisspeptin specifically enhanced reproductive function without altering other, non‐reproductive physiological responses to these environmental treatments. The inhibitory environmental conditions used in this study caused little if any decline in serum luteinizing hormone (LH) and testosterone over the course of the experiment. Kisspeptin treatment tended to exacerbate the decline in LH within individuals, but there were no significant effects of kisspeptin when comparing changes in the hormone levels amongst groups. The interesting outcome that kisspeptin enhanced testis mass, apparently independently of hypothalamic endocrine mechanisms, suggests the possibility of local kisspeptin action within the gonads. Overall, we show a functional role for kisspeptin in integrating complex environmental information to specifically support reproduction. Future work should focus on direct effects of kisspeptin at the gonadal level of the HPG axis as well as its interactions with the metabolic functions and other hormones involved in reproduction, e.g., gonadotropin‐inhibitory hormone (GnIH). A lay summary is available for this article. Abstract : Lay Summary